2011
DOI: 10.4239/wjd.v2.i3.41
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in diabetes mellitus: Possible cellular and molecular mechanisms

Abstract: Osteoporosis, a global age-related health problem in both male and female elderly, insidiously deteriorates the microstructure of bone, particularly at trabecular sites, such as vertebrae, ribs and hips, culminating in fragility fractures, pain and disability. Although osteoporosis is normally associated with senescence and estrogen deficiency, diabetes mellitus (DM), especially type 1 DM, also contributes to and/or aggravates bone loss in osteoporotic patients. This topic highlight article focuses on DM-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
125
1
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 66 publications
(91 reference statements)
8
125
1
11
Order By: Relevance
“…In the presence of DM, an impaired osteoblast function is observed, with a decrease in RUNX2 expression (5). The results of the present study demonstrated that the resistance training had an osteogenic potential, stimulating the expression of this immunomarker.…”
Section: Bone Densitometrysupporting
confidence: 51%
See 1 more Smart Citation
“…In the presence of DM, an impaired osteoblast function is observed, with a decrease in RUNX2 expression (5). The results of the present study demonstrated that the resistance training had an osteogenic potential, stimulating the expression of this immunomarker.…”
Section: Bone Densitometrysupporting
confidence: 51%
“…Miazgowski and Czekalski (4) demonstrated that diabetic patients had significantly lower BMD and an increased incidence rate of osteopenia and osteoporosis. Consequently, due to the lower BMD bone fractures are found to have an increased incidence in the presence of both types of diabetes (5). Moreover, lower biomechanical resistance, deficiency in bone mineralization after a fracture and decreased bone calcium and phosphate content were observed in induced diabetic animals (6).…”
mentioning
confidence: 99%
“…In obese patient with T2DM, there is an increasing load to the bone and insulin resistance resulting in hyperinsulinemia that will trigger bone formation. The influences of hyperglycemia on microvasculature, osteoclasts and osteoblasts, as well as the formation of advanced glycation end products will lead to the increased of bone resorption and inhibition of bone formation [2]. Bone density has positive relationship with levels of vitamin D, that reduce the risk of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the World Health Organization (WHO) estimates that people suffering from DM in 2025 will increase to 333 million in the world, and from 8.4 million in 2000 to about 21.3 million years 2030 in Indonesia. 1,2 Patients with DM can experience a variety of complications [1,2]. Also known that DM can affect the bone remodeling process which lead to bone disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a skeletal disorder characterized by an imbalance between bone resorption and bone formation, culminating in fragility fractures, pain and disability (1). Although the mechanisms involved are unclear, increasing evidence indicates that oxidative stress plays a role in the pathogenesis of osteoporosis (2,3).…”
Section: Introductionmentioning
confidence: 99%